OXYGEN ISOTOPE STUDY OF MID-OCEAN RIDGE HYDROTHERMAL FLUIDS: IMPLICATION FOR THE OXYGEN-18 BUDGET OF THE OCEANS - Jean-Baptiste P.; Charlou J.L.; Stievenard M. (My University, 1997)
New data are reported for the 18O composition of hot hydrothermal fluids from various sites with different tectonic settings. The measured δ18O, in the range 0.53-2.3%% confirm earlier data suggesting that mid-ocean ridge hydrothermal vents are a major source of 18O to the ocean. In light of this new data, we attempt to re-evaluate the marine 18O budget from direct quantification of the main sources and sinks of oceanic oxygen-18. Within the uncertainty of the flux estimates, 18O inputs and outputs are found to balance each other, showing that oceanic 18O is presently at a steady-state. Using these present fluxes, we examine the past evolution of the 18O composition of the ocean and speculate that the initial 18O oceanic content may have evolved rapidly towards its present value. This suggests, as already pointed out in previous studies, that ocean water may have had a rather constant 18O composition over most of the Earth's history and that δ 18O measurements in ancient cherts and carbonates may primarily record the evolution of the ocean temperature.